A circular economy handbook : how to build a more resilient, competitive and sustainable business - Weetman, Catherine (London : Kogan Page, 2021)
"WINNER: 2018 Les Plumes des Achats & Supply Chain - The Committee Special Prize The growing global consumption of resources highlights that our current approaches to production and business are fundamentally flawed and will rapidly become outdated and problematic. Engaged businesses are now increasingly re-thinking product design, material choices, business models and supply chains, and adopting the principles of the circular economy. Through decoupling resources from consumption, products and materials remain in use, waste is reduced and cost-savings are increased. A Circular Economy Handbook is the comprehensive guide to the circular economy and is designed to help the reader create future-fit, sustainable strategies moving forward. Now in its second edition, A Circular Economy Handbook provides a holistic framework for the design of supply chain and supporting business models and includes tools the reader can use to generate ideas. Using real examples across a range of market sectors, this is a must-read for businesses, students and policymakers to understand the theory and fast-developing practice of the circular economy"--
"First published in Great Britain and the United States in 2017 as A Circular Economy Handbook for Business and Supply Chains by Kogan Page Limited"--Verso.
Includes bibliographical references and index.
Keywords: Recycling industry; Business logistics; Managerial economics